Conceptual Framework for the Formation of Low-carbon Development: Kazakhstan’s Experience - Bekturganova, Makpal; Satybaldin, Azimkhan; Yessekina, Bakhyt (International Journal of Energy Economics and Policy, 2018)
This study aims to analyze the theoretical assessment of formation of low-carbon development in Kazakhstan: the development of approaches and the identification of priority directions. The application of scientific methods in this research will allow studying the process of formation and development of low car-bon economy with the use of two methods. Institutional approach involves investigating of legislative and legal support. The ecological - economic approach, which assumes of analysis of efficiency of the directions and methods of decarbonization. This research confirms that Kazakhstan requires formation and development of low-carbon economy, but we have to understand clearly approaches and choose the correct mechanisms. Further, the authors developed three different approaches of transition to low-carbon development for Kazakhstan. According to the results of this theoretical study proposed that means the category for low-carbon development is a new socio-economic and technological system (model) of economic development that stimulates the reduction of greenhouse gas emissions. In Kazakhstan developed regulatory framework, but is far behind from goals and objectives. However, the system of mechanisms of transition to low-carbon development is at an early stage of formation and supplemented by a wide range of tools. Keywords: Low-Carbon Development, Decarbonization, Energy Resources JEL Classifications: Q 40, Q 49 DOI: https://doi.org/10.32479/ijeep.7294